Are athletics environmental? A study on whether being an athlete affects how on view and engages in pro-environmental behaviour - Low, Zheng Yu (Nanyang Technological University, 2021)
Organized sports can have many impacts on the local and global environment (Schmidt, 2006) which could stem from the greenhouse emissions of athletes’ participation in various competitions (Wharton, 2013). While sports organizations could put in measures to curb the environmental impact of major organized sports events, the success would be dependent on the various stakeholders involved. Athletes, being a primary stakeholder (Mendizabal et al., 2020), contribute directly to the impact on the environment. As such, there was a need to understand how athletes view the environment and if there was a difference in their views and behaviours towards the environment from the general population. A sample of athletes from various institutes of higher learning like National University of Singapore, Nanyang Technological University etc., were recruited to take part in the study. People who did not engage in sports competitively were recruited to form up the sample of the general population as well. Participants were made to answer questions from the New Ecological Paradigm (NEP) scale (Anderson, 2012) to measure their views towards the environment as well as the Scale of Environmentally Responsible Behaviour (SERB) (Lee et al., 2013) to measure on the prevalence of their environmentally-friendly behaviours. Due to factors like an athlete’s competitiveness, normative influence, and the time constraints faced by athletes, they would be less likely to care for the environment and engage in pro-environmental behaviours. Gender would also affect how environmental the athletes were and how much pro-environmental behaviours they engaged in. However, results found that there were no significant statistical differences in the NEP and SERB scores between athletes and general population. While there was a statistical significant difference in the NEP scores between male and female athletes, their SERB scores were of no statistical significant difference.